2016
DOI: 10.1073/pnas.1518644113
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell movement of mitochondria in plants

Abstract: We report cell-to-cell movement of mitochondria through a graft junction. Mitochondrial movement was discovered in an experiment designed to select for chloroplast transfer from Nicotiana sylvestris into Nicotiana tabacum cells. The alloplasmic N. tabacum line we used carries Nicotiana undulata cytoplasmic genomes, and its flowers are male sterile due to the foreign mitochondrial genome. Thus, rare mitochondrial DNA transfer from N. sylvestris to N. tabacum could be recognized by restoration of fertile flower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…Another possible explanation for these phenomena is cell fusion since during fusions of plant cells lacking cell walls (called protoplasts) the cytoplasms often segregate non‐randomly (Evans, ). In cell fusions between two varieties of Nicotiana , chloroplasts are present only from one parent but mitochondria recombine with each other (Belliard & Pelletier, ) similar to what has been reported at the graft junction (Gurdon et al., ). Protoplast‐like protrusions form at the graft junction (Jeffree & Yeoman, ; Melnyk et al., ) and it is possible that cells from the graft parents fuse together at the graft junction.…”
Section: Cell Adhesion and Cell Divisionsupporting
confidence: 78%
See 1 more Smart Citation
“…Another possible explanation for these phenomena is cell fusion since during fusions of plant cells lacking cell walls (called protoplasts) the cytoplasms often segregate non‐randomly (Evans, ). In cell fusions between two varieties of Nicotiana , chloroplasts are present only from one parent but mitochondria recombine with each other (Belliard & Pelletier, ) similar to what has been reported at the graft junction (Gurdon et al., ). Protoplast‐like protrusions form at the graft junction (Jeffree & Yeoman, ; Melnyk et al., ) and it is possible that cells from the graft parents fuse together at the graft junction.…”
Section: Cell Adhesion and Cell Divisionsupporting
confidence: 78%
“…Plasmodesmata can form between grafts of unrelated species (Kollmann & Glockmann, ) and might be important for promoting graft formation (Jeffree & Yeoman, ). Recent reports revealed that genetic material including nuclear, mitochondrial, and chloroplast genomes combine from the rootstock and scion at the graft junction to generate cells with genomes from both graft parents (Stegemann & Bock, ; Stegemann, Keuthe, Greiner, & Bock, ; Thyssen, Svab, & Maliga, ; Fuentes, Stegemann, Golczyk, Karcher, & Bock, ; Gurdon, Svab, Feng, Kumar, & Maliga, ). Fuentes et al.…”
Section: Cell Adhesion and Cell Divisionmentioning
confidence: 99%
“…The mitochondrial genome of a cybrid between two plants in the nightshade family (tobacco and henbane [Hyoscyamus niger]) had more than 35 regions of recombination between homologous sequences, ranging from 100 to 9,000 bp (Sanchez-Puerta et al, 2015). Recombination and coexistence of the mitochondrial genes from different species also were observed in (1) plants generated from the junction of grafted tissues (Fuentes et al, 2014;Gurdon et al, 2016), (2) parasitic plants whose mitochondrial genomes contained some host plant fragments (Davis and Wurdack, 2004;Sanchez-Puerta et al, 2017), and even (3) host plants, in which fragments of parasitic plant mitochondrial genomes were observed in the host mitochondrial genomes (Mower et al, 2004). Furthermore, horizontal gene transfer between nonrelated plants is more frequently observed in mitochondrial genomes than in nuclear and plastid genomes (Bergthorsson et al, 2003).…”
Section: Mitochondrial Fusionmentioning
confidence: 99%
“…For example, they still retain bacterial cyclic DNA. In addition, mitochondria and mitochondrial DNA can be horizontally transferred from cell to cell in mammalian cell culture systems and in plants [2,3,4]. There is, however, no definitive evidence to show whether this mitochondrial movement occurs in vivo in animals.…”
Section: Introductionmentioning
confidence: 99%